CMR assessment of the left ventricle apical morphology in subjects with unexplainable giant T-wave inversion and without apical wall thickness ≥15 mm. (19th January 2017) - Wu, Bailin; Lu, Minjie; Zhang, Yan; Song, Bo; Ling, Jian; Huang, Jinghan; Yin, Gang; Lan, Tian; Dai, Linlin; Song, Lei; Jiang, Yong; Wang, Hao; et al.
Abstract : Aims: Patients with unexplainable giant T-wave inversion in the precordial leads and apical wall thickness <15 mm have been reported. These patients cannot be diagnosed as apical hypertrophic cardiomyopathy (AHCM) according to the current criteria. The objective of this study was to evaluate the apical morphological features of this type of patients using cardiac magnetic resonance. Methods and results: Institutional ethics approval and written informed consent were obtained. A total of 60 subjects with unexplainable giant T-wave inversion and 76 healthy volunteers were prospectively enrolled in the study. The segmented left ventricular (LV) wall thickness was measured according to the American Heart Association 17-segmented model. The apical angle (apA) as well as the regional variations in LV wall thickness was analysed. Considerable variation in LV wall thickness in normals was observed with progressive thinning from the base to apex (male and female, P < 0.01). The apical thickness of subjects with giant T-wave inversion was 8.10 ± 1.67 mm in male, which is thicker than that of controls (4.14 ± 1.17 mm, P < 0.01). In female, the apical thickness was also significantly different from controls (5.85 ± 2.16 vs. 2.99 ± 0.65 mm, P < 0.01). Compared with normals, the apA decreased significantly in male (87.44 ± 13.86 vs.115.03 ± 9.90°, P < 0.01) and female (90.69 ± 8.84 vs. 110.07 ± 13.58°, P < 0.01) subjects, respectively. Conclusion: Although the absolute thickness of apical wall was below the current diagnostic criteria of AHCM, the apical morphological features of subjects with unexplainable giant T-wave inversion were significantly different from normals. Whether these subjects should be included into a preclinical scope of AHCM needs further investigations.